The Effect of Work Environment, Employee Training, and Leadership Style on Service Quality with Employee Performance as an Intervening Variable at Medium Customs Type, Customs and Excise Controlling and Servicing Office of Tanjung Perak - Hendy Surya Pratama; Sri Rahayu; Rifda Fitrianty (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to analyze the effect of work environment, employee training, and leadership style on service quality with employee performance as an intervening variable at Medium Customs Type, Customs and Excise Controlling and Servicing Office of Tanjung Perak. This study employed a quantitative approach with an explanatory research design. The population consisted of employees of the Customs and Excise Supervision and Service Office of Tanjung Perak, with a sample of 198 respondents. Data were collected using a questionnaire and analyzed using SEM-PLS. The results show that work environment, employee training, and leadership style have a positive and significant effect on employee performance. Work environment, employee training, leadership style, and employee performance also have a positive and significant effect on service quality. In addition, employee performance is proven to mediate the effect of work environment, employee training, and leadership style on service quality. These findings indicate that improving service quality is not only directly determined by organizational factors, but also through the improvement of employee performance. Therefore, the Medium Customs Type, Customs and Excise Controlling and Servicing Office of Tanjung Perak needs to strengthen a conducive work environment, practical employee training, supportive leadership, and reliable and responsive employee performance.